2017
DOI: 10.1111/ajt.14207
|View full text |Cite
|
Sign up to set email alerts
|

Donor Preconditioning After the Onset of Brain Death With Dopamine Derivate n-Octanoyl Dopamine Improves Early Posttransplant Graft Function in the Rat

Abstract: Heart transplantation is the therapy of choice for end-stage heart failure. However, hemodynamic instability, which has been demonstrated in brain-dead donors (BDD), could also affect the posttransplant graft function. We tested the hypothesis that treatment of the BDD with the dopamine derivate n-octanoyl-dopamine (NOD) improves donor cardiac and graft function after transplantation. Donor rats were given a continuous intravenous infusion of either NOD (0.882 mg/kg/h, BDD+NOD, n = 6) or a physiological saline… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 31 publications
(75 reference statements)
4
23
0
Order By: Relevance
“…A more recent retrospective study from New York in pediatric heart transplantation supported our findings and found that low‐dose donor dopamine was associated with a decreased risk of postoperative right heart failure, while the beneficial effect was offset at higher doses exceeding 5 μg/kg/min . Growing evidence from experimental studies indicates that dopamine or its derivative NOD is capable to preserve also cardiomyocytes from cold storage injury . In addition, dopamine increased the tolerance of lungs to withstand tissue damage from hypothermic preservation in an isolated ventilation/perfusion model of the rat.…”
Section: Effect On the Performance Of Non‐renal Graftssupporting
confidence: 79%
See 1 more Smart Citation
“…A more recent retrospective study from New York in pediatric heart transplantation supported our findings and found that low‐dose donor dopamine was associated with a decreased risk of postoperative right heart failure, while the beneficial effect was offset at higher doses exceeding 5 μg/kg/min . Growing evidence from experimental studies indicates that dopamine or its derivative NOD is capable to preserve also cardiomyocytes from cold storage injury . In addition, dopamine increased the tolerance of lungs to withstand tissue damage from hypothermic preservation in an isolated ventilation/perfusion model of the rat.…”
Section: Effect On the Performance Of Non‐renal Graftssupporting
confidence: 79%
“…46 Growing evidence from experimental studies indicates that dopamine or its derivative NOD is capable to preserve also cardiomyocytes from cold storage injury. 36,47,48 In addition, dopamine increased the tolerance of lungs to withstand tissue damage from hypothermic preservation in an isolated ventilation/perfusion model of the rat. Dopamine pretreatment stabilized endothelial barrier function of lungs subjected to prolonged cold ischemia and resulted in significant less edema formation upon re-warming.…”
Section: Effec T On the Performan Ce Of Non -Renal G R Af Tsmentioning
confidence: 99%
“…However, our results remain structurally similar if we add the hospital's and OPO's payoffs within the social planner's objective function. Also, apart from contractual levers, our model points to other potential operational interventions for improving organ recovery outcomes: increasing OR capacity (increasing l; Jendrisak et al 2002Jendrisak et al , 2005 4 , leveraging practices that reduce the sensitivity of organ quality to the delay experienced by the donor (decreasing q a ; Kotsch et al 2006, Li et al 2017, improving the waiting experience in the OR queue (decreasing c h ; Hall 2006, Pines et al 2008, and emphasizing HCP training to reduce the discomfort associated with organ recovery activities (decreasing c e ; DOT Grant Program Report 2005, Siminoff et al 2009).…”
Section: Resultsmentioning
confidence: 98%
“…This complicates showing differences between experimental groups after a certain time of reperfusion. Thus, it is accepted to measure hemodynamic relations after 60 minutes of reperfusion even though it is a shorter period than in clinical practice 14,[34][35][36][37][38] . Secondly, dosing or the mode of administration of riociguat might be different in a clinical setup.…”
Section: Discussionmentioning
confidence: 99%